People's Intention to Visit Tourist Destinations during the Covid-19 Pandemic in Surabaya - Umi Faricha Bascha; Adiana Mutamsari Witaningrum; Dwi Setiani Sumardiko; Dian Yuli Reindrawati (TIJAB (The International Journal of Applied Business), 2021)
The Covid-19 pandemic has affected tourism sectors, for example, resulting in social restrictions and travel restrictions. The declining number of tourists visiting tourist destinations has impacted cities for tourists including Surabaya. This paper aimed to analyze the Surabaya people's desire to make a leisure trip during the pandemic. A total of 121 questionnaires from 500 distributed ones which met the criteria were analyzed. The findings showed that the majority of Surabaya's residents had no intention of traveling during the pandemic as the Surabaya government implemented many travel restrictions, including large-scale social restrictions (LSSR) several times. The travel restrictions reduced the chance for traveling out of and into the Surabaya areas. The results of the questionnaires showed that green tourism would be the most chosen tourist destination by the respondents to visit if the pandemic calmed down. Culinary tours were placed in the second rank, followed by marine tourism and religious tourism. Suggestions for further research are that the government can provide more massive counseling about the importance of maintaining cleanliness. For instance, it needs to promote changing masks regularly and educating the public about the importance of Cleanliness Health Environment and Safety (CHSE) applied by all tourist destinations and other public places.